Bonus and Rebate: Perception of Exclusive GSM Dealers and Their Salesmen in Turkey - Karabiyikoglu, Melik (International Review of Management and Marketing, 2012)
The aim of this paper is to study bonus and rebate for exclusive dealers in GSM sector in Turkey, for which operators and handset manufacturers provide special incentives to dealers for exceeding specific sales targets. They develop a theoretical model of dealers and manufacturer behavior based on observations about key aspects of the mobile phone market. The analysis provides important insights about sales bonus. For example, rebate is not preferred by the owners of dealers instead of bonuses. The authors find empirical support when they test the theoretical results. Keywords: Bonus; Rebate; Dealer Incentive; GSM Sector; Channel Support JEL Classifications: M39; E32; L1; L81